Addressing the challenges of developing a socially sustainable urban district A case study of Frihamnen - BENGTSSON, ANNA; GRANBERG, ANNA (My University, 2017)
Due to growing segregation and inequalities in Gothenburg, issues concerning social sustainability have gotten increased focus in the ongoing urban development project RiverCity Gothenburg. The Frihamnen district is part of the project and some of the main objectives for the district is to create a diverse area, accessible for everyone, with socially mixed housing and a variation in activities and business. The purpose of this master thesis is to address the important aspects to consider when working with social sustainability in large urban development projects. The study is a qualitative study with an abductive approach with the Frihamnen project as the case study. A set of ten interviews and one observation constitute the results of the study. The results were thereafter discussed in relation to the developed theoretical framework. The identified challenges and hence important aspects to consider when incorporating social sustainability in urban development projects were concluded to be a collective development of the area, having predefined demands, managing the different actors to collaborate, having a supportive municipal organization and creating defined and measurable targets.
Keywords: Samhällsbyggnadsteknik; Civil Engineering